Torsional Irregularity Mitigation in Reinforced-Concrete SMRF Buildings Using Hybrid Steel-Braced Eccentrically Braced Frames with RC Beam Links: Effect of Link Length on Seismic Response - Roland Martin Simatupang; Carrissa Regina Shafi Candraningtyas (Asian Journal Science and Engineering, 2026)
Plan torsional irregularity can amplify edge displacement in reinforced-concrete (RC) buildings with asymmetrically distributed lateral stiffness. This numerical study evaluates a hypothetical educational-building model comprising six main stories and a roof level, an RC special moment-resisting frame, and an asymmetrically located RC evacuation-core wall. A hybrid inverted-V eccentric bracing system was introduced on the weaker facade; the diagonal braces were modeled using BJ37 structural-steel H 400 x 400 x 13 x 21 sections, while the intervening RC beam segment acted as the horizontal eccentric link. Four ETABS Ultimate v22.0.0 Build 3628 models were compared by linear-elastic response-spectrum analysis in accordance with SNI 1726:2019: an unbraced baseline and three braced variants with geometric link lengths of 0.50, 1.00, and 1.50 m. Among the three investigated variants, the 0.50 m model produced the lowest combined CM-CR eccentricity and critical edge displacement. In the final signed +/-5% accidental-eccentricity response-spectrum results, the uppermost comparable Joint 25 displacement decreased from 86.33 mm to 22.91 mm in the Y direction (73.5%) and from 65.27 mm to 28.73 mm in the X direction (56.0%). The fundamental period changed from 1.109 s for the baseline to 0.599 s, 0.672 s, and 0.755 s for the 0.50 m, 1.00 m, and 1.50 m variants, respectively. With 15 retained modes, cumulative UX/UY mass participation was 92.88%/95.76% for Model 1, 93.49%/95.26% for Model 2, 93.26%/95.69% for Model 3, and 93.19%/95.50% for Model 4. All four models exceeded 90% cumulative translational mass participation in both principal directions. The signed accidental-eccentricity cases were scaled independently to the applicable equivalent-static minimum base shear before the reported responses were extracted. The bracing system reduced the severity of the source-model torsional indices but did not eliminate torsional irregularity at every story and in both directions. Because the analysis was linear elastic and the link was an RC beam segment rather than a conventional steel EBF link, the results demonstrate comparative global-response trends only and do not establish nonlinear ductility, energy-dissipation capacity, connection adequacy, foundation adequacy, or construction readiness.